AB1038 Pharmacokinetics, pharmacodynamics and safety of nc-2500, a novel xanthine oxidoreductase inhibitor, in healthy japanese male subjects. (12th June 2018) - Hirano, M.; Kobayashi, S.; Miyayama, E.; Ohta, T.; Yamamoto, M.; Yamakawa, T.
Abstract : Background: Gout flare due to rapid urate reduction after initiating urate-lowering therapy (ULT) is one of the major issues in the therapy, which impairs patients' quality of life and adherence. For the prevention of it, the guidelines in the ACR, the EULAR and Japan recommend initiating ULT with a low starting dose followed by adequate titrations, however it is rare in clinical settings. NC-2500 is a novel orally active xanthine oxidoreductase (XOR) inhibitor in development for the treatment of gout/hyperuricemia. Preclinical studies showed that multiple doses increase the plasma concentration and enhance the urate-lowering effect of NC-2500, suggesting that NC-2500 may decrease the risk of gout flare when initiating the treatment. Objectives: The aim of this study was to evaluate the pharmacokinetics, pharmacodynamics and safety of NC-2500 in healthy Japanese male subjects. Methods: A Phase 1, randomised, single-blind, placebo-controlled, single and multiple ascending dose study was conducted. Each cohort consisted of 8 subjects, with 6 receiving NC-2500 and 2 receiving placebo orally. A total of 5 cohorts were studied in the single-dose study (10 mg to 160 mg, fasted conditions) and 4 cohorts were studied in the multiple-dose study (10 mg to 80 mg, fed conditions). The levels of NC-2500 and urate in plasma/serum and urine were assayed at predetermined time points. Safety and tolerability were assessed by physical examination, vital signs, electrocardiography, clinical laboratory tests and adverse events (AEs). Results: Following singe oral doses of NC-2500, maximum plasma concentration (Cmax) and area under the plasma concentration-time curve (AUC) increased approximately in a dose-proportional manner except that the increase in the Cmax at 160 mg was less than dose proportional. The time to reach the Cmax (Tmax, median) was at 2.0–3.5 hours post dose and food intake delayed the Tmax by 1 hour. In the presence of food, NC-2500 absorption appeared to decrease slightly or not be affected. Plasma NC-2500 concentration increased with multiple doses and the Cmax and AUC on Day 7 at 80 mg were 1.4–1.5 times higher than those on Day 1. NC-2500 was hardly excreted into the urine. Effects of NC-2500 on serum urate (sUA) levels were approximately dose-dependent. The sUA level in the single 160 mg dose cohort decreased by 1.03 mg/dL. Moreover, in the subjects receiving multiple doses of 80 mg, the sUA level decreased gradually over the 7 days with a decrease from baseline of 1.93 mg/dL. The incidence of AEs was similar between NC-2500 and placebo treatments and all AEs were mild in severity. Conclusions: From the results, NC-2500 is expected to have potential to resolve the issues of current ULT by its unique urate-lowering property to decrease acute flare, with no or minimal titrations. As for safety, NC-2500 was considered safe and well-tolerated. Furthermore, NC-2500 was hardly excreted through the kidneys, which can be a favourable profile for patients with renal impairment, frequently observed in gout. Acknowledgements: The authors thank T. Ryuno and H. Kumagai of Nippon Chemiphar Co. Ltd., for technical advice and support for the drug product development and manufacturing. Disclosure of Interest: M. Hirano Shareholder of: Nippon Chemiphar Co., Ltd., Employee of: Nippon Chemiphar Co., Ltd., S. Kobayashi Shareholder of: Nippon Chemiphar Co., Ltd., Employee of: Nippon Chemiphar Co., Ltd., E. Miyayama Employee of: Nippon Chemiphar Co., Ltd., T. Ohta Shareholder of: Nippon Chemiphar Co., Ltd., Employee of: Nippon Chemiphar Co., Ltd., M. Yamamoto Shareholder of: Nippon Chemiphar Co., Ltd., Employee of: Nippon Chemiphar Co., Ltd., T. Yamakawa Shareholder of: Nippon Chemiphar Co., Ltd., Employee of: Nippon Chemiphar Co., Ltd.